2015
DOI: 10.1186/s12958-015-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in the canine uterus and placenta: possible implications in pregnancy

Abstract: BackgroundLeptin (Lep) is known for its involvement in the regulation of reproductive functions. It is important for uterine receptivity, implantation, placental growth and maternal energy homeostasis in several species, but Lep’s function in the pregnant dog has not been investigated.MethodsPregnant bitches were ovariohysterectomized at pre-implantation, post-implantation, mid-gestation and prepartum luteolysis. Two additional groups were treated with aglepristone in mid-gestation, and ovariohysterectomized 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 75 publications
4
23
0
1
Order By: Relevance
“…Interestingly, human (Dötsch et al, ) rat (Kawai et al, ), and murine (Hoggard et al, ) placenta were found to be a source of leptin. More recently, Balogh et al () reported the gene expression of leptin and leptin receptor in the placenta of dogs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, human (Dötsch et al, ) rat (Kawai et al, ), and murine (Hoggard et al, ) placenta were found to be a source of leptin. More recently, Balogh et al () reported the gene expression of leptin and leptin receptor in the placenta of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Balogh et al () reported the expression of leptin and leptin receptor in the foetal and maternal sides of the placenta over the course of pregnancy. Their presence indicates multiple paracrine/autocrine functions (Balogh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Además, se ha descrito un descenso en las concentraciones séricas de leptina hacia el final de la gestación (Cardinali et al, 2017), así como también la expresión de genes de leptina (Lep) y de receptores Lep en úte-ro y placenta canina (Balogh et al, 2015), postulándose que el sistema de señalización de Lep tendría un rol en el mecanismo de parto de esta especie.…”
Section: Partounclassified